Internal structure of a large, complex rock glacier and its significance in hydrological and dynamic behavior: A case study in the semi-arid Andes of Argentina - Villarroel, Cristian Daniel; Ortiz, Diana Agostina; Forte, Ana Paula; Tamburini Beliveau, Guillermo; Ponce, Oscar David; Imhof, Armando Luis; López, Andrés (Permafrost and Periglacial Processes)
This paper presents an analysis of the internal structure, hydrogeology and dynamics of a large, complex, multilobate and multiroot rock glacier combining electrical resistivity tomography (ERT), hydrochemical data and differential interferometry synthetic aperture radar (DInSAR). The rock glacier consists of a series of overlapping lobes that represent different advancing stages with different degrees of conservation. The ERT surveys characterize the active layer and the upper part of the permafrost layer, the latter showing a heterogeneous geometry and electrical resistivity values ranging from 7 to 142 kΩm. Hydrochemical data argue for both the existence of different disconnected water flow pathways inside the rock glacier and the remarkable ionic concentrator effect of this landform. The horizontal displacement from October 2014 to April 2017 shows greatest magnitudes in the upper sector of both tongues, reaching speeds of up to 150 cm/year. The active frontal sector shows a displacement rate of 2–4.5 cm/year. This study contributes to knowledge of the material properties of rock glaciers, which are considered to represent important reservoirs/water resources, and their influence on the distribution of mountain permafrost, hydrology, and dynamics. Finally, to the best of our knowledge, the possible influence of the metal content of the ground on the resistivity values recorded for mountain permafrost is highlighted for the first time. Fil: Villarroel, Cristian Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - San Juan. Centro de Investigaciones de la Geosfera y Biosfera. Universidad Nacional de San Juan. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones de la Geosfera y Biosfera; Argentina Fil: Ortiz, Diana Agostina. Universidad Nacional de San Juan. Facultad de Ciencias Exactas, Físicas y Naturales. Departamento de Geofísica y Astronomía; Argentina. Universitat Bonn; Alemania Fil: Forte, Ana Paula. Consejo Nacional de ...